Faktor yang Berhubungan dengan Unmeet Need Kontrasepsi pada Pasangan Usia Subur di Puskesmas Kalahien - Anggraini, Farida; Kania, Nia; Febriana, Silvia Kristanti Tri; Suhartono, Eko; Triawanti (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Pregnancy and birth are not controlled can have a national impact due to unmet needs, apart from population explosion, it can also cause higher maternal and infant mortality rates related to unwanted pregnancies. Objective: To analyze factors related to the unmet need for contraception among couples of childbearing age at the Kalahien Community Health Center, South Barito Regency, in 2023. Methods: Quantitative research using a cross sectional approach. The sample in this study was female couples of childbearing age who were in the working area of the Kalahien Community Health Center. Sampling used non-probability sampling with purposive sampling technique was 95 people. Data was taken using a questionnaire. Data were analyzed using the chi square test and logistic regression test. Results: Obtained p-value for education variables (p=0.001 <α 0.05), level of religiosity (p=0.000 <α 0.05), access to health facilities (p=0.004 <α 0.05), and husband's support (p=0.001 <α 0.05) with unmet need for contraception. Conclusion: There is a significant relationship between education, level of religiosity, access to health facilities, and husband's support with unmet need for contraception, husband's support is the most dominant factor